2017
DOI: 10.4236/ajps.2017.84049
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylcellulase Activity in Lettuce Seeds Prior to Germination

Abstract: Does the endosperm pose a mechanical resistance on embryonic axis (radicle) growth for lettuce seed (achene) germination? To aid answering this question, the cell wall degrading enzyme, carboxymethylcellulase (CMCase) was extracted and assayed from lettuce seeds imbibed for 0 to 12 h, prior to germination. Measuring the loss of viscosity of carboxymethylcellulose, CMCase activity was high in dry seeds, low after 6 h of imbibition, high after 9 and 10 h, and then reduced again after 12 h. Fractions from Sephade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…In the present study, we showed that cellulase activity in the endosperm cap or radicle was higher than that in the lateral endosperm or the embryo with the radicle removed, respectively, indicating that cellulase activity is also tissue‐specific during lettuce seed germination. In addition, it was found that low‐salt extractable cellulase activity in the endosperm cap and radicle of lettuce seeds increased prior to the completion of germination, in agreement with the results of Pavlišta and Valdovinos (). Bewley et al () detected a low level of cellulase activity in the whole seeds, which did not increase prior to radicle protrusion.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we showed that cellulase activity in the endosperm cap or radicle was higher than that in the lateral endosperm or the embryo with the radicle removed, respectively, indicating that cellulase activity is also tissue‐specific during lettuce seed germination. In addition, it was found that low‐salt extractable cellulase activity in the endosperm cap and radicle of lettuce seeds increased prior to the completion of germination, in agreement with the results of Pavlišta and Valdovinos (). Bewley et al () detected a low level of cellulase activity in the whole seeds, which did not increase prior to radicle protrusion.…”
Section: Discussionsupporting
confidence: 90%